Potential of Liquid Smoke from Palm Kernel Shell as Biopreservative to Tuna (Thunnus sp) Fish Protein - Musrowati Lasindrang (Indonesian Association of Food Technologists, 2017)
The purpose of this research was to evaluate the role of liquid smoke of oil palm kernel as “ biopreservative” on the fish during storage toward chemistry/biochemical or microbiological change at to tuna (thunnus sp) fish.This research was carried out in three steps that is: 1) Making liquid smoke with temperature pirolysis 4000C during 90 minutes and liquid smoke fractionation in rank: F1 : liquid temperature 1000C; F2: 101 - 1250C; F3: 126 – 1500C; F4: 151 – 2000C. 2) Proximate analysis of liquid smoke FO and Fraction F2 to tuna fish that analysed with TVB, Total Bacterium, total protein content . The result indicates that the phenol and acid content was more increase with higher fractionation temperature while the carbonyl content was more reduced with higher fractionation temperature. The TVB value for Tuna fish muscle without soaking higher liquid smoke (38.93 mg N/100g and 36.27 mg N/100g) compared to tuna fish muscle of liquid smoke soaking (F0) that is 13.87 mg N/100g and 11.73 mg N/100g and also soaking with F2 fraction muscle tuna 12.27 mg N/100g. Total bacterium (2.67 x 109 cfu/g and 2.10 x 109 cfu / g) compare without soaking liquid smoke (F0) and F2 fraction that is (8.43 x 105cfu/g and 6.23 x 105 cfu /g) and (8.57 x 105 cfu/g and 6.50 x 105 cfu/g).